Exposure Assessment for Toxic Hepatitis Caused by HCFC-123 - Ki-Woong Kim; Hae Dong Park; Konghwa Jang; Jiwon Ro (Elsevier, 2018)
This case report attempts to present a case of acute toxic hepatitis in fire extinguisher manufacturing workers exposed to 2,2-dichloro-1,1,1-trifluoro-ethane (HCFC-123) in August 2017 in Korea. Twenty-two-year-old male workers were exposed to HCFC-123 for 1.5 hours one day and for 2.5 hours the other day, after which one worker died, and the other recovered after treatment. The workers were diagnosed with acute toxicity of hepatitis. However, exposure levels of HCFC-123 were not known with no work environment measurement done. Therefore, this study was conducted to estimate the exposure concentration of HCFC-123 via a job simulation experiment. In the simulation, the HCFC-123 exposure concentration was measured with the same working practice and working time as with the workers aforementioned. As a result, the workers who infused HCFC-123 into storage tanks were estimated to be exposed to HCFC-123 at a concentration of 20.65 ± 10.81 ppm, and a mean concentration of area samples within a working radius were estimated as 70.30 ± 18.10 ppm. Valve assembly workers working on valves of a fire extinguisher filled with HCFC-123 were exposed to HCFC-123 at concentrations of 91.65 ± 4.03 ppm and 115.55 ± 7.28 ppm, respectively, in the simulation, and area samples simulated within the working radius were also found to be high with concentrations of 122.75 ± 91.15 ppm and 126.80 ± 60.25 ppm, respectively. Nitrogen gas packing workers, who did not handle HCFC-123 directly, were exposed to the agent at a concentration of 71.80 ± 8.49 ppm. These results suggest that exposure to HCFC-123 at high concentrations for 1.5-2.5 hours caused acute toxic hepatitis in two workers. Keywords: Acute toxic hepatitis, HCFC-123, Workers